In vivo biodistribution of carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles in rats - Pereira, Vitor H. (2011)
Carboxymethylchitosan/poly(amidoamine) dendrimer nanoparticles (CMCht/PAMAM) have recently been proposed for intracellular drug delivery purposes. These are constituted by a PAMAM dendrimer core grafted with chains of CMCht. Previous reports have shown that these nanoparticles disclosed an improved cytotoxic profile when compared to traditional dendrimers. Following on these results the present study aims to assess, for the first time, the short-term in vivo biodistribution of CMCht/PAMAM dendrimer nanoparticles upon intravenous injections in Wistar Han rats. The rats were injected in the tail vein with 1 and 10 µg/g, respectively, of fluorescein isothiocyanate (FITC) labeled CMCht/PAMAM dendrimer nanoparticles. Brain, liver, kidney and lung were collected at 24, 48 and 72 hours after injection and further stained with phalloidin-TRITC (red) and DAPI (blue) to trace the nanoparticles within the tissues. Liver, kidney and lung were also stained for haematoxylin and eosin in order to assess possible alterations in the morphology of these organs. CMCht/PAMAM dendrimer nanoparticles were observed within the vascular space and parenchyma of liver, kidney and lung, and in the choroid plexus, after 24, 48 and 72 hours upon intravenous injection of nanoparticles. No particles were observed in the brain parenchyma, nor any apparent deleterious histological changes, were observed within these organs. The present report revealed that CMCht/PAMAM dendrimer nanoparticles were stable in circulation for periods up to 72 hours, targeting the main organs/systems through internalization by the cells present in their parenchyma. These results provide positive indicators to their potential use in the future as intracellular drug delivery systems.